2009
DOI: 10.5194/bg-6-2861-2009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of the iron supply to phytoplankton in the Southern Ocean: a model study

Abstract: Abstract. An upgraded version of the biogeochemical model SWAMCO is coupled to the ocean-sea-ice model NEMO-LIM to explore processes governing the spatial distribution of the iron supply to phytoplankton in the Southern Ocean. The 3-D NEMO-LIM-SWAMCO model is implemented in the ocean domain south of latitude 30° S and runs are performed over September 1989–December 2000. Model scenarios include potential iron sources (atmospheric deposition, iceberg calving/melting and continental sediments) as well as iron st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 90 publications
(125 reference statements)
6
125
10
Order By: Relevance
“…Thus, iron is taken up from sea water when ice forms and is released back to the ocean when it melts. Lancelot et al (2009) have studied the impact of this source in the Southern Ocean and shown that it is of primary importance in the seasonal ice zone. Their approach relies on the modeling of iron concentration within sea ice.…”
Section: Iron From Sea Icementioning
confidence: 99%
“…Thus, iron is taken up from sea water when ice forms and is released back to the ocean when it melts. Lancelot et al (2009) have studied the impact of this source in the Southern Ocean and shown that it is of primary importance in the seasonal ice zone. Their approach relies on the modeling of iron concentration within sea ice.…”
Section: Iron From Sea Icementioning
confidence: 99%
“…Because sea ice and icebergs play an important role in offshore iron transport in the Southern Ocean (Smith et al, 2007;Lannuzel et al, 2008;Lancelot et al, 2009), a reduction of their production rates will change the spatial pattern of the iron supply. Recent studies have suggested that ice sheets and melt water play a role in supplying iron to the ocean (Raiswell et al 2008;Wadham et al 2013;Bhatia et al, 2013); the inclusion of such sources in numerical models (e.g., Death et al, 2013) is potentially important because the high latitudes are experiencing rapid warming.…”
Section: Other Factors Changing the Iron Cycle In The Future Oceanmentioning
confidence: 99%
“…Physical processes that may contribute to the supply of new iron include upwelling (de Baar et al, 1995), vertical diffusive flux , horizontal advection (Ellwood et al, 2008;Sedwick et al, 2008;Bowie et al, 2009), the interaction between bathymetry and currents (Blain et al, 2007;Sokolov et al, 2007), and mesoscale eddies and cross-frontal mixing (Kahru et al, 2007). In addition, the melting of sea ice and icebergs also can supply or redistribute iron in surface waters (Smith et al, 2007;Lannuzel et al, 2008;Lancelot et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Understanding why iron accumulates in sea ice depends on a better understanding of sea ice multiphase physical processes and how they interact with biogeochemical processes. The storage and transport of iron associated with sea ice dynamics is important because it may stimulate summer phytoplankton blooms in the Southern Ocean, as shown by a preliminary model investigation of the Southern Ocean (Lancelot et al, 2009). Overall, the sea-ice habitat appears to be highly productive and is thought to make a significant contribution to the carbon, sulfur and iron cycles, which needs to be carefully assessed.…”
Section: Introductionmentioning
confidence: 99%